(untitled) (Research, Society and Development, 2022)
Introduction: ethics is an integral part of the philosophy responsible for investigating the principles that motivate, distort or guide human behavior. In the field of nursing, professional practice transcends direct care, it goes beyond the care provided, it needs to be based on science and ethical-moral knowledge. Objective: to report the experience of creating and implementing an Institutional Nursing Ethics Committee. Methodology: this is a descriptive study, of the experience report type, based on the authors’ experience while working in the Nursing Management service of a public hospital in the city of Rio de Janeiro. data collection took place through the experience of two nurses, in the year 2021. Results: the creation and implementation of the nursing ethics committee arose from a mandatory demand and concern of one of the authors, since the unit had more than 50 nursing professionals working in the service. After the election, the ethics committee was established according to specific resolution nº 593/201, with the work of 5 nursing professionals, 3 nurses and 1 nursing technician and 1 nursing assistant. Final considerations: this unique experience was important for the health service and its professionals as it made it possible to make them aware that ethical issues are part of the daily life of the profession and that they can protect nursing actions, generating gains for patients, family members, professionals and managers.